2020
DOI: 10.33429/cjas.10219.3/6
|View full text |Cite
|
Sign up to set email alerts
|

A Text Mining Analysis of Central Bank Monetary Policy Communication in Nigeria

Abstract: This paper employs text-mining techniques to analyse the communication strategy of the Central Bank of Nigeria (CBN) during the period 2004-2019. Since the policy communique released after each meeting of the CBN’s monetary policy committee (MPC) represents an important tool of central bank communication, we construct a corpus based on 87 policy communiques with a total of 123, 353 words. Having processed the textual data into a form suitable for analysis, we examined the readability, sentiments, and topics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Second, it has been shown that the LDA yields superior outcomes in terms of generating semantically meaningful topics as well as assigning texts to the identified topics (Debortoli et al, 2016;Chang et al, 2009). Third, it has been used extensively in different applications, including Tumala and Omotosho (2019) for monetary policy communication in Nigeria; Omotosho (2020) for monetary policy communication in Ghana; and Hansen et al (2018) for monetary policy communication in the US. More importantly, the LDA allows not only for identifying the hidden topics, but also to estimate the degree to which each topic is reflected in the corpus.…”
Section: Analysing User Experience Of Mobile Banking Applications In Nigeriamentioning
confidence: 99%
“…Second, it has been shown that the LDA yields superior outcomes in terms of generating semantically meaningful topics as well as assigning texts to the identified topics (Debortoli et al, 2016;Chang et al, 2009). Third, it has been used extensively in different applications, including Tumala and Omotosho (2019) for monetary policy communication in Nigeria; Omotosho (2020) for monetary policy communication in Ghana; and Hansen et al (2018) for monetary policy communication in the US. More importantly, the LDA allows not only for identifying the hidden topics, but also to estimate the degree to which each topic is reflected in the corpus.…”
Section: Analysing User Experience Of Mobile Banking Applications In Nigeriamentioning
confidence: 99%